Catalytic electron drives host–guest recognition. Issue 18 (20th April 2022) - Owatari, Yoshihiro; Iseki, Shuta; Ogata, Daiji; Yuasa, Junpei
Abstract : The reactants of AQH–CH2 CN are converted into AQ and CH3 CN in sustainable electrocatalytic chain reactions, successfully achieving catalytic electron-triggered charge-transfer (CT) complex formation. Abstract : Electron injection is demonstrated to trigger electrocatalytic chain reactions capable of releasing a solvent molecule and forming a redox active guest molecule. One-electron reduction of a hydroxy anthrone derivative (AQH–CH2 CN) results in the formation of an anthraquinone radical anion (AQ˙ − ) and acetonitrile (CH3 CN). The resulting fragment of AQ˙ − exhibits high stability under mild reducing conditions, and it has enough reducing power to reduce the reactant of AQH–CH2 CN. Hence, subsequent electron transfer from AQ˙ − to AQH–CH2 CN yields the secondary AQ˙ − and CH3 CN, while the initial AQ˙ − is subsequently oxidized to AQ. Overall, the reactants of AQH–CH2 CN are completely converted into AQ and CH3 CN in sustainable electrocatalytic chain reactions. These electrocatalytic chain reactions are mild and sustainable, successfully achieving catalytic electron-triggered charge-transfer (CT) complex formation. Reactant AQH–CH2 CN is non-planar, making it unsuitable for CT interaction with an electron donor host compound (UH Ant2 ) bearing parallel anthracene tweezers. However, conversion of AQH–CH2 CN to planar electron acceptor AQ by the electrocatalytic chain reactions turns on CT interaction, generating a host CT complex with UH Ant2 (AQ ⊂ UH Ant2 ). Therefore, sustainable electrocatalytic chain reactions can control CT interactions using only a catalytic amount of electrons, ultimately affording a one-electron switch associated with catalytic electron-triggered turn-on molecular recognition.